PENGEMBANGAN MEDIA POP-UP BOOK RUMAH ADAT PADA MATERI KERAGAMAN BUDAYA KELAS IV SD - Ahmad Syaikhoni; Yeri Sutotpo; Supriyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
IPAS is one of the subjects taught in grade IV at the elementary school level in the Independent Curriculum. In the IPAS learning, there is social studies content that teaches material on Indonesian cultural diversity, discussion of the diversity of traditional houses in Indonesia. IPAS learning can be taught through methods and media that are appropriate for the level of cognitive development. Grade IV of elementary school is included in the stage of concrete operational cognitive development. The problem found is the lack of adequate media according to the development stage of students to support the learning of traditional house diversity materials. The purpose of this study is to determine the characteristics, feasibility, and practicality of traditional house pop-up book media on the cultural diversity material of grade IV elementary school students. Where pop-up book media can be used because it is in accordance with the stage of concrete operational cognitive development in grade IV of elementary school. This study uses aresearch and development (R&D) research design with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The results of the study show that the pop-up book learning media of traditional houses is declared very feasible based on the assessment of media expert validators with an average feasibility score of 4.84 in the aspect of graphic assessment. Furthermore, based on the assessment of the validator of the media material expert, the pop-up book of the traditional house was declared very feasible with an average score of 4.70 for the feasibility of the content, 4.84 for the linguistic feasibility and 4.63 for the contextual aspect. Meanwhile, based on the practicality test of the pop-up book media, traditional houses received an assessment score in the assessment aspects which included the appearance, presentation of materials, and benefits received a score of 100% and was included in the very practical category which was supported based on the results of the calculation of the reproduction coefficient of 1 > 0.90, and the scalability coefficient (Ks) of 1 > 0.60, so that it met the practicality criteria.